Conceptual Framework on Resource Availability and Performance of MSE in Africa: A Case of Jinja District, Uganda - Tom, Baligeya; Charles Richrd, Kaggwa; Joseph, Ntayi (Open Journal of Business and Management, 2021)
Micro and Small-Scale Enterprises (MSE) are important in almost all developing economies in the world, characterized by unemployment, import dependency and income distribution challenges. Establishing Micro and Small-Scale Enterprises (MSE) is not blowing pressure through a basket; rather it is about having innovations, inventions and sharing ideas. It takes more than what we think about an idea of establishing a startup. It is significantly important that excellent planning and management of the available resources is critical for start-up success. We look forward to discussing about availability and performance of MSE.
Keywords: MSE Performance; Resource Availability; Human; Financial; Material